2022
DOI: 10.33394/j-ps.v10i2.4822
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student's Logical Thinking Abilities And Learning Outcomes Through Guided Inquiry Model

Abstract: The abilities of students can affect learning outcomes. One capability that is closely related to learning outcomes is the ability to think logically which improves students’ understanding of knowledge. This study aims to determine cognitive learning outcomes and logical thinking ability of students in science subjects through the guided inquiry learning model. The quasi-experimental research was conducted with a non-equivalent pretest-posttest control group design. The population was all students of seventh g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Facilities must meet standards and be adapted to the school's capabilities. All parties are invited to participate in maintaining and preserving existing facilities (Murtaufiq, 2020;Yuliana et al, 2022). The results of interviews with students show that various facilities and infrastructure greatly help learning activities.…”
Section: Discussionmentioning
confidence: 99%
“…Facilities must meet standards and be adapted to the school's capabilities. All parties are invited to participate in maintaining and preserving existing facilities (Murtaufiq, 2020;Yuliana et al, 2022). The results of interviews with students show that various facilities and infrastructure greatly help learning activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a clear picture shown by the studies which reveal that motivation brings a significant impact towards students' learning motivation. It is continued by the studies that motivation has a strong impact towards students' learning outcomes (Effendi, 2016;Yuliana et al, 2022). It is also found that learning motivation has a positive relation with students' learning independence in which it influences students to do independent learning (Moh Ghoizi Eriyanto et al, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…Keterampilan berpikir kritis ialah satu dari keterampilan metakognitif yang signifikan dengan tuntutan pendidikan abad 21 yang wajib siswa kuasai (Aulia & Aulia Zahroh, 2021;Dewi et al, 2021). Proses belajar siswa dianjurkan untuk mengembangkan keterampilan berpikir kritisnya, sebab merupakan landasan dasar untuk memahami konsep IPA dalam pembelajarannya (Supandi & Senam, 2019;Yuliana et al, 2022). Faktanya keterampilan berpikir kritis siswa di Indonesia perlu ditingkatkan sebab masih tergolong rendah, hal tersebut di tujukkan dari hasil studi, yakni peringkat 38 dari 42 negara pada TIMSS 2011 dan juga peringkat 44 dari 49 negara dalam bidang matematika dan peringkat ke 46 dari 49 negara dalam bidang sains pada TIMSS 2015 (Fatra et al, 2022;Rahayu & Dewi, 2022).…”
Section: Pendahuluanunclassified